1997
DOI: 10.1111/j.1528-1157.1997.tb01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Modeling in Epilepsy Surgery Candidates

Abstract: Summary:Purpose: The validity and clinical significance of dipole modeling in epilepsy surgery candidates is not fully established.Patients and Methods: Interictal and ictal dipole modeling was performed in 43 patients with refractory complex partial seizures (CPS) and intracranial structural abnormalities demonstrated with optimum magnetic resonance imaging (MRI: space-occupying, n = 15; atrophic, n = 26; dysplastic, n = 2). Video-EEG monitoring showed CPS in all patients. In 12 patients, additional intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 18 publications
3
40
0
2
Order By: Relevance
“…Similar dipole results for interictal epileptiform activity in patients with mesiotemporal epilepsy have been obtained in our previous investigations (Lantz et al, 1996(Lantz et al, , 1997, and the similarity between ictal and interictal dipole results has also been demonstrated by other investigators (Boon et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar dipole results for interictal epileptiform activity in patients with mesiotemporal epilepsy have been obtained in our previous investigations (Lantz et al, 1996(Lantz et al, , 1997, and the similarity between ictal and interictal dipole results has also been demonstrated by other investigators (Boon et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Ebersole (1994) found the early ictal rhythms of mesiotemporal seizures to have a strong vertical dipole component, whereas lateral temporal neocortical seizures could be modeled mainly by radial dipoles. Boon et al (1997) found similar differences between ictal dipoles in patients with temporal (mostly medial) lesions compared with patients with extratemporal neocortical lesions. In this investigation, dipole reconstruction of the ictal patterns localized the activity to one temporal lobe, with a specific oblique posterior and elevated dipole orientation (the OPE pattern) that was quite reproducible between patients.…”
Section: Discussionmentioning
confidence: 56%
“…In conclusion, scalp EEG has the potential to offer more spatial and temporal information [1,[7][8][9]. These techniques are more sophisticated and require more in-depth training and experience for proper application and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Several noninvasive and interictal diagnostic approaches have been implemented in the presurgical evaluation programs in intractable epilepsy syndromes of uniregional origin, all of them with the intention (a) to add to the complementary information about a regional functional deficit or morphologic lesion corresponding to the hypothesized primary epileptogenic zone, and (b) to reduce the number of invasive EEG recordings (26)(27)(28)(29). For this purpose, the most promising aspect of EEG dipole-source analysis is the theoretic possibility to ameliorate the poor spatial resolution of spikes recorded from the scalp in depth.…”
Section: Discussionmentioning
confidence: 99%